100 tinig sa iisang himig - Taylan, Lhai R. (Quezon City Central Book Supply, Inc., 2012)
aStudents' testimony about their experience with De La Salle University, Philippines; collection of articles.
In Tagalog, and some articles in English.
Keywords: De La Salle University -- Centennial, celebration; Universities and colleges -- Philippines